1982
DOI: 10.1063/1.444334
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric relaxation studies in polyvinyl butyral

Abstract: Dielectric measurements have been made in thick films (∼100 μm) of polyvinyl butyral (PVB) having degree of polymerization n=1600, in the frequency range 100 Hz–100 KHz and temperature range 300–373 K. The results indicated that PVB was in the amorphous phase and observed dielectric dispersion has been assigned as the β-relaxation process. The β relaxation is of Debye type with symmetrical distribution of relaxation times. The dielectric relaxation strength Δε and the distribution parameters β̄ increase with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…3) with an activation energy of 11.1 AE 0.2 kcal mol À1 , which is close to the values previously derived from dielectric data for PVB 10 (12 kcal mol À1 ) and for poly(vinyl alcohol) (PVA) 41,42 (B13 kcal mol À1 ). A value of the activation energy of 13 kcal mol À1 was also reported for b relaxation in PVB by Mehendru et al, 13 but the motional correlation times were considerably lower than those found by us and other authors. 10 On the other hand, the correlation times here determined are in agreement with those reported for b relaxation in amorphous PVA.…”
Section: Dielectric Spectroscopysupporting
confidence: 74%
See 1 more Smart Citation
“…3) with an activation energy of 11.1 AE 0.2 kcal mol À1 , which is close to the values previously derived from dielectric data for PVB 10 (12 kcal mol À1 ) and for poly(vinyl alcohol) (PVA) 41,42 (B13 kcal mol À1 ). A value of the activation energy of 13 kcal mol À1 was also reported for b relaxation in PVB by Mehendru et al, 13 but the motional correlation times were considerably lower than those found by us and other authors. 10 On the other hand, the correlation times here determined are in agreement with those reported for b relaxation in amorphous PVA.…”
Section: Dielectric Spectroscopysupporting
confidence: 74%
“…As far as the dynamic properties of PVB are concerned, dielectric spectroscopy (DS) investigations were reported quite long ago, sometimes in combination with mechanical measurements. [10][11][12][13] However, the results shown in the different publications seem incoherent, possibly because of the different, often unspecified, PVB composition and/or the different sample treatments. More recently, DS data were reported only at a few temperatures above the PVB glass transition in comparative studies of pristine PVB and PVB either UV irradiated 14 or loaded with alumina particles.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of the large number of technological applications, only a few studies were reported concerning the dynamics of PVB [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. Recently, PVB dynamics was investigated by some of us over broad frequency and temperature ranges by DS and 1 H field-cycling (FC) NMR relaxometry, focusing on a commercial sample [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Dhaliwal and Hay Mehendru et al., Iwasaki et al.have recently reported the relationships between such properties of PVB as dielectric relaxation and structure. 2325 PVB, which is amorphous and transparent, exhibits good adhesive properties. Moreover, it makes composite soft, flexible and easy to be clipped.…”
Section: Introductionmentioning
confidence: 99%